Gambaran Pelaksanaan Komunikasi Terapeutik Oleh Perawat Di Ruang Rawat Inap RSUD Tamiang Layang - Septi Machelia Champaca Nursery (Jurnal Kaharati, 2022)
The implementation of therapeutic communication has not been carried out optimally because nurses often focus only on the main things such as communication of nursing actions and forgetting things that are considered trivial such as forgetting to introduce themselves, maintaining eye contact when communicating, and others. Poor therapeutic communication will create a bad image for the hospital. This study aims to identify the description of the implementation of therapeutic communication by nurses in the inpatient room at Tamiang Layang Hospital. This type of research is quantitative, using a descriptive research design. The population is all nurses in the Inpatient Room at Tamiang Layang Hospital, as many as 75 people. The sample is 43 with a simple random sampling technique. Data analysis through univariate analysis using a frequency distribution table. The results showed that therapeutic communication by nurses in the inpatient room at Tamiang Layang Hospital had been implemented well, as many as 37 people (86%). Most of the pre-interaction therapeutic communication stages have been carried out well as many as 38 people (88.4%), the introduction stage was carried out well as many as 22 people (51.2%), the work stage was carried out well as many as 24 people (55.8%) and The termination stage of therapeutic communication was carried out well as many as 34 people (79.1%). This study concludes that therapeutic communication by nurses in the inpatient room at Tamiang Layang Hospital has been carried out well.